PENGABDIAN MASYARAKAT BERBASIS POTENSI PENDIDIKAN, PELATIHAN, DAN PENYULUHAN DI MI “LITERACY” MIFTAHUL HUDA WAJAK DAN SMK DHARMA WANITA 02 WAJAK - Yanti, Verida; Yazidah, Nok Izatul; Napfiah, Siti; Kartika, Era Dewi (Universitas Muhammadiyah Tangerang, 2024)
Potential-Based Community Service (PMBP) includes education, training, and service which are the Tri Dharma of Higher Education. PMBP activities are important to continue to be carried out by students, the purpose of PMBP is to develop the personality of the students themselves